2020
DOI: 10.21203/rs.3.rs-46190/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Role of Medication Beliefs on Medication Adherence in Hypertensive Middle Eastern Refugees and Migrants in Australia

Abstract: BackgroundAdherence to medication is essential in some patients for achieving treatment control in hypertension. Medication beliefs is one of the personal modifiable factors that has been recognised to influence medication adherence in different populations. However, there is no published research to confirm the relationship between medication beliefs and medication adherence in Middle Eastern refugees and migrants in Australia. These two different groups may develop different beliefs about their medications t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Specifically in this study, participants highlighted the importance of shared conversations with pharmacy professionals around medication excipients, alcohol‐content and religious festivals that affect adherence to medications (including periods of fasting). Perspectives raised in the workshops echoed those in the wider literature, where a person's medicines‐taking behaviour and subsequent access to medicines services can be influenced by their culture 37–40 . To enable culturally appropriate conversations and support the delivery of culturally competent medicines consultations, participants recognized the need to underpin community pharmacy service design and delivery with improved staff training.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Specifically in this study, participants highlighted the importance of shared conversations with pharmacy professionals around medication excipients, alcohol‐content and religious festivals that affect adherence to medications (including periods of fasting). Perspectives raised in the workshops echoed those in the wider literature, where a person's medicines‐taking behaviour and subsequent access to medicines services can be influenced by their culture 37–40 . To enable culturally appropriate conversations and support the delivery of culturally competent medicines consultations, participants recognized the need to underpin community pharmacy service design and delivery with improved staff training.…”
Section: Discussionmentioning
confidence: 94%
“…Perspectives raised in the workshops echoed those in the wider literature, where a person's medicines-taking behaviour and subsequent access to medicines services can be influenced by their culture. [37][38][39][40] To enable culturally appropriate conversations and support the delivery of culturally competent medicines consultations, previously been identified, 41 and questions have been raised about the format, content and optimization of this training too. [42][43][44][45][46] In the updated standards for the initial education and training of pharmacists, the General Pharmaceutical Council placed emphasis on equality, diversity and inclusion to address health inequalities.…”
Section: Discussionmentioning
confidence: 99%
“…Almost half of the studies were conducted in the United States of America (7 out of 15 studies) [11][12][13][14][15][16][17]. 3 studies recruited participants from Australia [18][19][20], 2 studies from Korea [4,21], and 1 each from the Netherlands [22], Spain [23], and Jordan [24].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Tere are few studies addressing factors associated with medicine adherence in immigrants and refugees [11][12][13][14][15][16][17][18][19][20][21][22][23][24], and several studies focus on medicine nonadherence in general populations or concentrate on self-care and management of medicines or treatment [25][26][27][28]. Although this is the case, current evidence suggests that there is little evidence published that addresses the numerous factors involved in medication nonadherence in immigrants and refugees.…”
Section: Introductionmentioning
confidence: 99%
“…It also reported that patients with "acceptance" belief showed the highest rate of medication adherence and patients with "doubt" belief showed the lowest rate of medication adherence. Performing clinical interventions and targeted counseling can make a positive change in beliefs and medication adherence [24]. Chin et al (2021) demonstrated that Health-related knowledge and health literacy lead people to use the medication more wisely [25].…”
Section: Discussionmentioning
confidence: 99%